Brand Revitalization of the Declining Mobile Phone Brand via Brand Ambassadors and Product Innovation. - Abbas, Syed Ali (2024)
While Nokia led the industry for quite a long, its decline stage is alarming. Catering to the need to revitalize the brand, the study aims to develop a rebranding strategy for Nokia. In terms of scope, the study is correlational with quantitative methods being employed for hypothetical-deductive investigation. Results depict the significant impact of brand ambassadors and the positive relation of product innovation measures to revitalize the brand Nokia. The interlinkage of brand ambassadors’ influence with a focus on product innovation strategies, especially for a declining mobile phone brand is a rare practice in academic research. The research is beneficial not only for the intended brand but also for brands in similar businesses facing such kinds of scenarios. The scope of the study can be huge by incorporating a Global audience, though limited in this study as far as sample region is concerned. DOI: https://doi.org/10.54663/2182-9306.2024.SpecialIssueMD.69-85